Thinking the empire whole. Issue 4 (2nd October 2019) - Pincus, Steven; Bains, Tiraana; Reichardt, Alyssa Zuercher
Abstract: Most scholarship on the British empire in the eighteenth century tends to focus on the empire's relationship with one or another region that would later become a nation-state. We argue that imperial subjects, imperial actors, and those resisting the empire rather understood this phenomenon as a global actor. Nevertheless, there was never a single, unified British imperial project. From the late seventeenth century, competing visions of empire coalesced into partisan politics that spanned the empire. Key debates focused on political economy. Understanding this partisan dynamic is essential for coming to grips with British politics, colonial resistance, and the lives of Indigenous peoples.